2021
DOI: 10.3390/math9172071
|View full text |Cite
|
Sign up to set email alerts
|

Educating Adults with a Location-Based Augmented Reality Game: A Content Analysis Approach

Abstract: With the exception of Pokémon Go, relatively little is known about other Mobile Augmented Reality (MAR) games, and the attitudes of middle-aged and elderly adults towards them are hitherto poorly examined. The aim of this research is to examine the opinions of young, middle-aged, and elderly adults about the location-based MAR game Ingress. The responses to questions related to Ingress were collected from 24 adult players aged 20–60 from Greece and subsequently were analyzed by means of content analysis, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…However, the negativity of elder generations toward such games that has been identified in other research [46] may progressively disappear once they become more familiar with these games [47,48]. This lack of negativity in attitudes of elder adults (52+) was also observed in previous research with Ingress [49,50].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, the negativity of elder generations toward such games that has been identified in other research [46] may progressively disappear once they become more familiar with these games [47,48]. This lack of negativity in attitudes of elder adults (52+) was also observed in previous research with Ingress [49,50].…”
Section: Discussionsupporting
confidence: 55%
“…By applying content analysis and concept maps as techniques of qualitative research in order to measure the users' responses to questions related to Ingress, it was found through central concepts that the space was part of themselves; by playing Ingress, they left their personal mark in the space, while the educational use of augmented reality was also emphasized. It was also found that there was a differentiation of the answers in question 1 between age groups with age groups agreeing in pairs, the first two (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) with the last two (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and (50-60), while in question 2, there was an overlap in the responses of participants among age groups. In addition, methodologically, it is shown that content analysis and concept maps present the educational researcher with several advantages as they help to better visualize the links and subfields that emerge from interviews and participants' responses.…”
Section: Discussionmentioning
confidence: 95%
“…Two games now dominate the pervasive games market: Pokémon GO and Ingress [9]. Ingress has a rather simple core loop and low polish, but its dynamics seem to be tailored to enforce team socializing and collaboration [10]. After the successor to Ingress, Pokémon GO offers a more complicated primary gameplay loop.…”
Section: Introductionmentioning
confidence: 99%